2011
DOI: 10.1179/026708410x12687356948391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single and duplex surface treatments on wear properties of CP-Ti

Abstract: Wear behaviours of nitrided, anodised and duplex treated commercially pure (CP)-Ti were investigated using a pin on disc tribotester. First, CP-Ti was nitrided and then anodised at different temperatures and times. Phase structure, cross-section and surface hardness of coatings were examined with XRD, SEM and microhardness tester. Formation of TiN and anatase phases were observed after nitriding and anodising respectively. Thickness of the oxide layer along with hardness increased with increasing the anodisati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Similar studies supported that oxidation reduced the friction coefficient of titanium. Alsaran and Albayrak [23] studied the wear properties of single anodizing at different process parameters and anodizing on pre-nitrided Cp-Ti. They showed that while friction coefficient value of the untreated sample is 0.5, this value reduced to 0.26 after anodizing depending on process parameters.…”
Section: Tribological Propertiesmentioning
confidence: 99%
“…Similar studies supported that oxidation reduced the friction coefficient of titanium. Alsaran and Albayrak [23] studied the wear properties of single anodizing at different process parameters and anodizing on pre-nitrided Cp-Ti. They showed that while friction coefficient value of the untreated sample is 0.5, this value reduced to 0.26 after anodizing depending on process parameters.…”
Section: Tribological Propertiesmentioning
confidence: 99%
“…2d). Also, it is important to mention here that the significant reduction in COF of composite coated substrate may be resulted from the considerable increase in some vital properties of formed film especially structure stability, surface hardness, film thickness [29] and roughness [30].…”
Section: Wear Characteristicsmentioning
confidence: 99%
“…Studies show that conditions such as the deposition process and load can affect the coefficient of friction of hard coatings [21,22]; therefore, studying the effect of friction coefficient on damping has significance in engineering. Simulations were performed with different friction coefficients, constant stress ( σ x = -160 MPa, σ y = 100 Mpa), and constant frequency (100 Hz); and the energy dissipation and loss factor were calculated from the hysteresis curve.…”
Section: Microscopic Defects Extraction and Finite Element Modelling ...mentioning
confidence: 99%